Synthesis of Copper Matrix Hybrid Composites with Boron-, Nitrogen-, and Silicon-Doped Reduced Graphene Oxide by Hot Press Technique: Investigation of Tribological, Mechanical, and Electrical Conductivity Properties - Macit, Cevher Kursat; Horlu, Merve; Aksakal, Buenyamin; Er, Yusuf (Wiley-V C H Verlag Gmbh, 2025)
Copper and its alloys are widely used in the preparation of metal matrix composites due to their thermal and electrical conductivity. This study aims to improve the mechanical, tribological and electrical conductivity properties of copper (Cu) matrix powders by adding certain amounts (10 wt%) of reduced graphene oxide (rGO) nanopowder, boron (B), nitrogen (N) and silicon (Si) reinforced rGO nanopowder. Hybrid composites were produced by powder metallurgy production methods. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX) and Fourier-transform infrared spectroscopy (FT-IR) analysis for reinforcement, homogeneity and phase identification. The mechanical and tribological properties of the hybrid composites were investigated by hardness, wear tests and temperature dependent electrical conductivity tests to determine the effect of the reinforcement materials on the Cu matrix structure. The maximum hardness value was obtained from the (Cu-rGO-Si-B-N) hybrid composite with an increase of 193% compared to the pure Cu sample. When the coefficient of friction values of RGO and reinforced rGO hybrid composites were examined, a 219.12% lower coefficient of friction value was observed in the (Cu-rGO-Si-B-N) sample compared to the pure Cu sample. The highest value was observed in the temperature dependent electrical resistance analysis in the rGO reinforced sample.
Keywords: copper matrix hybrid composites; electrical conductivities; hot pressing; powder metallurgies; reduced graphene oxides